Perceptions of Junior and Senior High School Physical Education Teachers About the Quality of Physical Education in Semarang City - Rofa Ichsandi; Setyawati, heny; Yudha Kusuma , Donny Wira (Journal of Physical Education and Sports, 2024)
Quality of physical education specifically in the city of Semarang has not been identified. In this research, we examine the quality of physical education from the perspective of physical education teachers using Quality Physical Education Assessment analysis through 8 indicators. This research is a type of survey research using a mixed method approach. The research location is in Semarang City with the target being teachers from all junior high school and senior high school in Semarang City. The sampling technique uses total sampling and multistage random sampling. The data collection instruments were carried out using questionnaires, interviews, observation and documentation. Data analysis uses Quality Physical Education Assessment with the Excel program. Research results: 1) Skill Development and Bodily Awareness got an average score of 4.0 in the high category with a percentage of 77%, 2) Facilities and Norms in Physical Education got an average score of 4.26 in the high category with a percentage 90%, 3) Quality Teaching of Physical Education gets an average score of 4.18 in the high category with a percentage of 86%, 4) Plan for Feasibility of Physical Education gets an average score of 3.54 in the medium category with percentage 49%, 5) Social Norms and Cultural Practice gets an average score of 3.66 in the medium category with a percentage of 61%, 6) Governmental Input for Physical Education gets an average score of 4.14 in the high category with percentage 86%, 7) Cognitive Skill Development got an average score of 4.02 in the high category with a percentage of 81%, 8) Habituated Behavior in Physical Activity got an average score of 3.99 in the high category with a percentage of 77 %. The conclusion is that the quality of physical education is in the high category on 6 indicators and in the medium category on 2 indicators. The advice given by researchers is for teachers, government and stakeholders to continue to support and increase activities that improve the quality of physical education in general and specifically.